การทำรหัสลับแบบ AES บนหน่วยประมวลผลหลายแกนเพื่อเพิ่มประสิทธิภาพ - ศุภชัย ทองสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
AES (Advanced Encryption Standard) algorithm is a block encryption algorithm, established by the U.S. National Institute of Standards and Technology (NIST) in 2001. It has been adopted by many data security systems and now used worldwide. Most of AES implementations are for single-core processors. To achieve high performance for large data, this work proposed an AES algorithm for multi-core processors. Using parallelism inherent in large data, all cores are working concurrently to speed up the task.